Proinflammatory macrophages impair skeletal muscle differentiation in obesity through secretion of tumor necrosis factor‐α via sustained activation of p38 mitogen‐activated protein kinase. Issue 3 (27th September 2018) - Wang, Xueqiang; Zhao, Daina; Cui, Yajuan; Lu, Shemin; Gao, Dan; Liu, Jiankang
Abstract : Obesity is associated with skeletal muscle loss and impaired myogenesis. Increased infiltration of proinflammatory macrophages in skeletal muscle is noted in obesity and is associated with muscle insulin resistance. However, whether the infiltrated macrophages can contribute to obesity‐induced muscle loss is unclear. In this study, we investigate macrophage and muscle differentiation markers in the quadriceps (QC), gastrocnemius, tibia anterior, and soleus muscles from obese mice that were fed a high‐fat diet for 16 weeks. Then, we examined the effect and mediator of macrophage‐secreted factors on myoblast differentiation in vitro. We found markedly increased levels of proinflammatory macrophage markers (F4/80 and CD11c) in the QC muscle compared with the other three muscle groups. Consistent with the increased levels of proinflammatory macrophage infiltration, the QC muscle also showed a significant reduction in the expression of muscle differentiation makers MYOD1 and myosin heavy chain. In in vitro studies, treatment of C2C12 myoblasts with Raw 264.7 macrophage‐conditioned medium (CM) significantly promoted cell proliferation and inhibited myoblast differentiation. Neutralization of tumor necrosis factor α (TNF‐α) in Raw 264.7 macrophage CM reversed the reduction of myoblast differentiation. Finally, we found that both macrophage CM and TNF‐α induced sustained activation of p38 mitogen‐activated protein kinase (MAPK) in C2C12 myoblasts. Together, our findings suggest that the increased infiltration of proinflammatory macrophages could contribute toward obesity‐induced muscle loss by secreting inflammatory cytokine TNF‐α via the p38 MAPK signaling pathway. Abstract : Increased macrophage infiltration and reduced mass were observed in quadriceps muscle of high‐fat diet‐fed obese mice. Tumor necrosis factor‐αmediates the inhibitory effect of macrophages on C2C12 myoblast differentiation by sustained activation of p38 mitogen‐activated protein kinase